2006
DOI: 10.1364/oe.14.008103
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a fast method for high resolution phase contrast tomography

Abstract: We report the implementation of a method which can yield the 3D distribution of the phase (refractive index) of a weakly absorbing object from a single tomographic data set. In order to reduce the residual absorption artifact (due to the fact that only one data set is used) the original algorithm presented by A. V. Bronnikov is amended by adding in the filter a factor found by using a semi empirical approach. The quality of the reconstruction is largely sufficient for optimal segmentation and further postproce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
142
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 161 publications
(143 citation statements)
references
References 22 publications
1
142
0
Order By: Relevance
“…Absorption contrast data sets were reconstructed using regridding techniques [11]. The modified Bronnikov algorithm was applied for the reconstruction of the phase contrast data sets [12]. 3D-visualizations were obtained using the software Imaris (Bitplane, Zürich, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…Absorption contrast data sets were reconstructed using regridding techniques [11]. The modified Bronnikov algorithm was applied for the reconstruction of the phase contrast data sets [12]. 3D-visualizations were obtained using the software Imaris (Bitplane, Zürich, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…as suggested by Groso et al (2006), who named this algorithm the Modified Bronnikov Algorithm (MBA). A similar algorithm, the TIE phase retrieval, was derived by Paganin et al (2002) and successfully applied by Mayo et al (2003).…”
Section: Pc-ct Based On Pbimentioning
confidence: 99%
“…By adding in the denominator an absorption dependent correction factor, the filter is renormalized at zero frequencies and it has been shown that the residual artifacts induced by the nonzero absorption of real samples can be successfully eliminated [6]. This approach allows obtaining information about mixed, weakly absorbing-phase objects.…”
Section: Modified Transport Of Intensitymentioning
confidence: 99%